A coarse‐grained basin floor turbidite system – the Jurassic Los Molles Formation, Neuquen Basin, Argentina. Issue 7 (13th August 2020) - Giacomone, Gabriel; Olariu, Cornel; Steel, Ron; Shin, Moonsoo
Abstract: Coarse‐grained turbidite systems have been broadly described mostly on tectonically active basins, but there is lack of a detailed depositional and facies model in relatively unconfined settings. A large outcrop of the Los Molles Formation in Neuquen Basin is used to build the architecture, hierarchy and facies distribution of a coarse‐grained turbidite system. A high‐resolution satellite image, drone imagery and 4000 m of deposits measured in 20 locations with detailed facies description are used to build isopach and net to gross maps that allowed reconstruction of the system. The turbidite system is composed of five lobe complexes (each averaging 40 m thick). Each lobe complex is composed of two to six lobes (each averaging 5 m thick) that are formed by bed‐sets interpreted as basin floor distributary channels and unconfined flows. The lobe complexes show an overall aggradational pattern with minor progradation and retrogradation of the system and they also tend to stack compensationally in an autocyclic manner. The main characteristics of the system are: along lobe depositional‐axis, beds are thick and coarse with a high proportion of channels and high density turbidites, and 70 to 100% net:gross. In contrast, off depositional‐axis, beds are thinner, and fine to medium‐grained sandstone beds dominate; there is higher proportion of low density turbidites, and 30 to 70% net:gross. Lobe complexes are elongated (8 km wide and up to 20 km long), have high thinning rates (9 m km −1 on average) and at their distal end present finger‐like geometries. These deposits potentially represent good hydrocarbon reservoirs in the subsurface and therefore it is important to consider key aspects such as: (i) the proximity to the axis of the system; higher net:gross translates into fewer mud heterogeneities that could compartmentalize the reservoirs; (ii) geometry is elongated and serrated, and sand pinch‐outs might not occur homogenously; and (iii) topographic influence might decrease the risk of hydrocarbon leakage up‐dip.